Немонетарні показники інфляції:вагомість,зв’язок та місце у класифікації - Лосева, О.Г.; Пономаренко, О.О. (Культура народов Причерноморья, 2013)
Висвітлені немонетарні показники інфляції, шляхом вивчення класифікацій. Встановлене
місце та проаналізована вагомість показників за допомогою коефіцієнта Пірсона. Результатом роботи
є систематизація знань щодо класифікацій причин виникнення інфляції, та опис немонетарних причин
інфляції через встановлення вагомості цього показника. У роботі інтерпретовані значення коефіцієнта
кореляції Пірсону, які відбивають тісноту зв'язку між індексом інфляції і вибраними немонетарними
причинами. Освещены немонетарные показатели инфляции, путем изучения классификаций.
Установлено место и проанализирована значимость показателей с помощью коэффициента Пирсона.
Результатом работы является систематизация знаний относительно классификаций причин
возникновения инфляции, и описание немонетарных причин инфляции через установление весомости
этого показателя. В работе интерпретированы значения коэффициента корреляции Пирсона, которые
отражают тесноту связи между индексом инфляции и выбранными немонетарными причинами. Not monetary indicators of inflation, by studying of classifications are shined. The place is
established and the importance of indicators by means of Pearson's coefficient is analysed.
In work a number of methods of scientific research is used: analytical method, method of synthesis and scientific
abstraction, generalization, modeling and systematization.
Result of work is systematization of knowledge concerning classifications of the reasons of emergence of
inflation, and the description of not monetary reasons of inflation through establishment of ponderability of this
indicator.
In work values of coefficient of correlation of Pearson which reflect narrowness of communication between an
index of inflation and the chosen not monetary reasons are interpreted.
The strategy of selection of not monetary reasons constructed thus gives the chance not only qualitatively and
quantitatively to estimate their place at classifications. That further it is possible to apply classifying the
inflation reasons as a whole.